2021
DOI: 10.3748/wjg.v27.i31.5126
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic diagnosis and treatment of gastric dysplasia and early cancer: Current evidence and what the future may hold

Abstract: Gastric cancer accounts for a significant proportion of worldwide cancer-related morbidity and mortality. The well documented precancerous cascade provides an opportunity for clinicians to detect and treat gastric cancers at an endoscopically curable stage. In high prevalence regions such as Japan and Korea, this has led to the implementation of population screening programs. However, guidelines remain ambiguous in lower prevalence regions. In recent years, there have been many advances in the endoscopic diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 191 publications
(224 reference statements)
0
41
0
Order By: Relevance
“…Gastric cancer is one of the common malignant tumors. The early detection, diagnosis, and treatment of gastric cancer play an important role in improving the survival rate of gastric cancer and reducing medical expenditure [ 19 ]. At present, China still faces the situation of large population and uneven distribution of medical resources, so the feasibility of recommending all patients to carry out gastroscope screening for gastric cancer is relatively poor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gastric cancer is one of the common malignant tumors. The early detection, diagnosis, and treatment of gastric cancer play an important role in improving the survival rate of gastric cancer and reducing medical expenditure [ 19 ]. At present, China still faces the situation of large population and uneven distribution of medical resources, so the feasibility of recommending all patients to carry out gastroscope screening for gastric cancer is relatively poor.…”
Section: Discussionmentioning
confidence: 99%
“…The new gastric cancer screening scoring system has been established in the expert consensus opinion of the early gastric cancer screening project in China [ 16 , 19 ]. The Chinese new gastric cancer screening scoring system include 5 variables with a total score of 23: (1) age: 0 for 40-49, 5 for 50-59, 6 for 60-69, and 10 for >69; (2) sex: 4 for male and 0 for female; (3) H. pylori infection (Hp antibody test): positive 1 and negative 0; (4) PGR (serum pepsinogen I/II ratio): ≥3.89 is 0 and <3.89 is 3; and (5) G-17 (gastrin 17): less than 1.50 is 0, 1.50-5.70 is 3, and greater than 5.70 is 5 ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…With the continuous development of endoscopic technologies, artificial intelligence (AI) in the field of endoscopy has become a new area of interest. One study by Hirasawa et al, which utilized convolutional neural networks to detect EGC in endoscopic images, showed that the sensitivity of AI for white light endoscopy and magnifying NBI were 92% and 97%, respectively [ 35 ]. Meanwhile, a study done by Niikura et al did not show inferiority nor superiority of AI when compared to expert endoscopists [ 36 ].…”
Section: Artificial Intelligencementioning
confidence: 99%
“…Gastric cancer is also the second leading cause of cancer deaths in China, with a standardized 5-year survival rate of only 27.4% ( 3 ). According to related research, there were approximately 1 million newly diagnosed gastric cancer cases in 2008, 47% of which were in China, which accounted for half of the global gastric cancer deaths ( 4 , 5 ). Of note, however: the 5-year survival rate of early gastric cancer (EGC) was over 90%, which was much higher than that of advanced gastric cancer (AGC) (30%) ( 6 8 ).…”
Section: Introductionmentioning
confidence: 99%